Nikolai V. Krogius: A life-long chess game - Elena V. Ryaguzova (Saratov State University, 2022)
The article is devoted to the life and work of Nikolai Vladimirovich Krogius who was an international grandmaster (1964), European champion as part of the team (1965); two-time champion of the RSFSR (1952, 1964); Doctor of Psychological Sciences (1980), Head of the Department of Psychology of SSU (1978-1980), head of the Department of Chess of SCOLIPE (State Central Order of Lenin Institute of Physical Education) (1981-1983), Head of the Chess Department of the USSR State Sports Committee (1981-1989), Vice-President of FIDE (1986-1990). The objective of the article is to reflect on the life and creative work of Nikolai Vladimirovich viewing it as a successful chess game. The article presents several stages: the debut, including his childhood and studies in Saratov, his passion for chess and the first chess victories, studies at the Faculty of Philosophy of LSU; middlegame devoted to teaching in Saratov, serious sports and coaching work, doctoral dissertation defense, responsible management activities in the USSR State Sports Committee and FIDE; endgame including retirement, participation and prizes in the World Chess Championships among veterans, moving to New York, publishing books, articles and memoirs. The article pays special attention to the scientific activity of N. V. Krogius and the issues that are in the focus of his research interest. It shows theoretical and practical significance of his scientific works for the development of social and sports psychology, as well as the psychology of chess, which was founded in Russia by N. V. Krogius.